IMPLEMENTASI ALGORITMA KRIPTOGRAFI BLOWFISH UNTUK PENGAMANAN FILE BERBASIS DESKTOP - Winda; La Surimi; Ilham Julian Efendi (AnoaTIK: Jurnal Teknologi Informasi dan Komputer, 2025)
This research aims to implement the Blowfish cryptographic algorithm in a desktop-based file security application, to enhance user data confidentiality and security. Blowfish, as a symmetric block cipher, was chosen for its effectiveness in encrypting 64-bit data through 16 rounds of the Feistel function. The encryption process involves the use of P-array and S-box tables, as well as XOR and modulo 2^32 addition operations. The developed application supports various file formats, including PDF, TXT, JPG, PNG, MP3, and MP4, with a maximum size limit of 50 MB. The research methodology uses Rapid Application Development (RAD) to accelerate the development cycle, with stages including user requirements planning, design, iterative development, and testing. White box testing is applied to verify the implementation of the Blowfish algorithm and application functionality. Avalanche effect analysis is performed to evaluate the algorithm's sensitivity to small changes in input, ensuring robust data security. The test results show that the Blowfish algorithm was successfully implemented, with each application function running as expected. The avalanche effect proves that small changes in input produce significant changes in the encryption output, indicating a high level of security. This application is designed to operate offline and has a user-friendly interface, making it accessible to users with various levels of technical expertise.